A comparison of different methods for the determination of glomerular filtration rate in elderly patients with chronic renal failure - TOPUZOĞLU, AHMET; GÖKCE, İBRAHİM (SPRINGER, 2011)
The aim of the present study was to asses the accuracy of prediction equations in elderly patients with advanced renal disease (ARD). Twenty-three elderly patients (> 60 years) with chronic kidney disease (CKD) stages 3-5 underwent technetium-99 m-diethylenetriaminepentaacetic acid (Tc-99m-DTPA) radionuclide measurement of glomerular filtration rate (GFR). To predict GFR, estimation formulas [Cockcroft-Gault (CG), 6-variable Modification of Diet in Renal Disease (6-var-MDRD) and the corrected 24-hour creatinine clearance (24-h CCL) method] were used. Estimates of bias and precision were obtained to compare prediction equations of GFR with standard radionuclide measurement. In the present study, all the prediction equations overestimated the GFR measured with the radionuclide method. Six-var-MDRD and 24-h CCL methods correlated better with standard radionuclide measurements compared to the CG formula (Rc of 0.53 and 0.50 vs. 0.41, respectively) as for GFR prediction, but they were still insufficiently accurate. Glomerular filtration rate prediction equations correlate poorly with standard radionuclide measurements and their use may lead to late initialization of renal replacement therapy in elderly patients with ARD. Therefore, measurement by standard radionuclide method (Tc-99m-DTPA) is recommended to accurately assess GFR in elderly patients with ARD.
Keywords: Glomerular filtration rate; Cockcroft-Gault; Modification of Diet in Renal Disease; DTPA clearance; Advanced renal disease; CHRONIC KIDNEY-DISEASE; SERUM CREATININE; COCKCROFT-GAULT; EQUATIONS; GFR; TC-99M-DTPA; PERFORMANCE; PREDICTION; DIET; CLEARANCE